Analysis of Inventory Management for Medical Mask During the Covid-19 Pandemic at X Pharmacy in Yogyakarta - Grace, Admin; Aghniya, Asyifa (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Medical masks are the main personal protective equipment that must be owned by the general public and medical personnel for daily use during the COVID-19 pandemic. Thus, the problem of shortage of medical masks in pharmacies arises because of the high demand among medical personnel and the public. The research objectives are to analyze the inventory management of medical masks, and the impacts, obstacles, and solutions that X Pharmacy has implemented during the COVID-19 pandemic. This research used a qualitative method with pharmacy managers and health workers as research informants who were directly involved in pharmacy during the pandemic. The data analysis technique in this research used content analysis to make a summary and to create an overview of the characteristics of the meshat have been delivered by informants. The research shows that X Pharmacy experienced a shortage of medical mask stocks at the beginning of the pandemic and made efforts to restore the stocks of medical mask to fulfill consumer needs. Pharmacy also use the Pareto ABC method to determine inventory levels and to make it easier for pharmacy to replenish medical mask stocks.